The Public Interest in Iraqi Law (The Peerian Journal, 2025)
This study provides an in-depth analysis of the concept of public interest in Iraqi law as a foundational principle for administrative decisions, public service regulation, and administrative control, particularly under exceptional circumstances. It addresses the legal ambiguity surrounding the definition and application of public interest, the discretionary power of administrative authorities, and the role of the State Council and administrative judiciary in ensuring legal oversight and preventing abuse of power. The research emphasizes the necessity of reinforcing judicial independence to maintain the balance between safeguarding individual rights and pursuing collective benefit. It concludes with recommendations to enhance legislative and institutional frameworks related to public interest